Answer:
x=4/3
Step-by-step explanation:
2+4=2(x-1) original
6=2(x-1) combine like terms
6=2x-2 multiply x-1 by 2
8=2x add 2 to both sides
4=x divide both sides by 2
Answer:

Step-by-step explanation:
Using the rule of exponents
=
, then
=
= 
Answer:
B
Step-by-step explanation:
x² + 9x
to complete the square
add ( half the coefficient of the x- term )² to x² + 9x
= x² + 2(
)x + (
)²
= x² + 9x +
← the value of c
= (x +
)² ← a perfect square
0 ≠ 4. The equation is wrong, and has no true solution.
8x + 3 - 10x = -2(x - 2) + 3
<em><u>Distributive property.</u></em>
8x + 3 - 10x = -2x + 4 + 3
<em><u>Combine like terms.</u></em>
-2x + 3 = -2x + 7
<em><u>Cancel like terms.</u></em>
<em><u>Subtract 3 from both sides.</u></em>
0 ≠ 4
Answer:
8.55 × 
Step-by-step explanation: